2016
DOI: 10.1158/1078-0432.ccr-15-2379
|View full text |Cite|
|
Sign up to set email alerts
|

Prevention of Colitis and Colitis-Associated Colorectal Cancer by a Novel Polypharmacological Histone Deacetylase Inhibitor

Abstract: Purpose: Colorectal cancer is a worldwide cancer with rising annual incidence. Inflammation is a well-known cause of colorectal cancer carcinogenesis. Metabolic inflammation (metaflammation) and altered gut microbiota (dysbiosis) have contributed to colorectal cancer. Chemoprevention is an important strategy to reduce cancer-related mortality. Recently, various polypharmacologic molecules that dually inhibit histone deacetylases (HDAC) and other therapeutic targets have been developed.Experimental Design: Prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 52 publications
1
16
0
1
Order By: Relevance
“…Results showed that the ETBF-infected AOM/DSS mice given HSD (8%) exhibited significantly decreased polyp numbers compared to the ETBF-infected AOM/DSS mice given NSD ( Figure 5B,C). As previously reported, increased colon inflammation is positively associated with reduced colon length and increased spleen weight in the colitis-promoted tumorigenesis model [31,32]. Consistent with this observation, HSD (8%) + ETBF/AOM/DSS mice showed an increase in colon length ( Figure 5D) and a decrease in spleen weight ( Figure 5E) compared to NSD + ETBF/AOM/DSS mice.…”
Section: High Salt Diet Reduced Etbf-mediated Tumorigenesis In Azoxymsupporting
confidence: 89%
“…Results showed that the ETBF-infected AOM/DSS mice given HSD (8%) exhibited significantly decreased polyp numbers compared to the ETBF-infected AOM/DSS mice given NSD ( Figure 5B,C). As previously reported, increased colon inflammation is positively associated with reduced colon length and increased spleen weight in the colitis-promoted tumorigenesis model [31,32]. Consistent with this observation, HSD (8%) + ETBF/AOM/DSS mice showed an increase in colon length ( Figure 5D) and a decrease in spleen weight ( Figure 5E) compared to NSD + ETBF/AOM/DSS mice.…”
Section: High Salt Diet Reduced Etbf-mediated Tumorigenesis In Azoxymsupporting
confidence: 89%
“…Although further studies are still needed to understand whether the decrease of protein Kac levels may contribute to the depletion of SCFA producers or not in CD patients, the findings in this study indicate that lysine acetylation might be a potential target for manipulating the growth and functional activity of SCFA producers, and thereby for the treatment of diseases such as CD. Accordingly, previous studies have shown that lysine deacetylase (KDAC) inhibitors, such as butyrate, suberyolanilide hydroxamic acid (SAHA), valproic acid (VPA), and statin hydroxamate, effectively treat colitis in animal models [50][51][52][53] . In particular, Wei et al reported that statin hydroxamate alleviated colitis and reduced the blood endotoxin (lipopolysaccharide) level 51 , an indicator of dysbiosis of gut microbiota 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that various KDAC inhibitors, such as butyrate, suberyolanilide hydroxamic acid (SAHA), valproic acid (VPA) and statin hydroxamate, effectively treat colitis in animal models [3841]. In particular, Wei et al reported that statin hydroxamate alleviated colitis and reduced the blood endotoxin (lipopolysaccharide) level [39], an indicator of dysbiosis of gut microbiota [42]. Although the mechanism has been attributed to their beneficial effects on the intestinal epithelium cells, our findings indicate that the KDAC inhibitors may in part directly interact with the microbiome for the alleviation of intestinal colitis.…”
Section: Discussionmentioning
confidence: 99%